Indigenous Scheming and Manufacturing of a Laboratory Scale Heat Treatment Furnace - Technical Report - Wahaj, M.; Asim, M.; Owais, A. W.; Waqas, A. W.; ul Hasson, S. Anwar (Journal of the Institute of Engineering, 2017)
In order to contribute in the research activities related to heat treatment of metals and other engineering materials, a laboratory scale heat treatment furnace is essentially required. Among several other types of furnaces, electric heat treatment furnace is said to be most useful. It is provided with a programmable controller which precisely controls heating rate, soaking time and cooling rate. The controller also helps in keeping the heat treatment safe by emergency turnoff facility. This manuscript reports the indigenous designing and development of electrical heat treatment furnace, which not only provides enormous learning to fresh graduates but also saved a handsome amount, which could have spent in purchasing same article from commercial market. In this paper, the sequential procedure of furnace designing and development is being shared with the engineering community so that the researchers of under developed countries may save their esteemed educational and research funds. Journal of the Institute of Engineering, 2016, 12(1): 151-161